Nicotiana tabacum as a dead-end trap for adult Diaphorina citri: A potential biological tactic for protecting citrus orchards - Zheng, Lixia; Xu, Qianqian; Gong, Gu; Liao, Yonglin; Yu, Min; Shabala, Sergey; Chen, Wensheng; Wu, Weijian (Frontiers in Plant Science, 2023)
The Asian citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Liviidae), is a key vector of the causal agents of Huanglongbing (HLB), a devastating disease affecting citrus almost worldwide. Nicotiana tabacum L. is an important commercial crop in China. Field observations suggested that D. citri adults die on N. tabacum leaves when grown nearby citrus orchards. In this study, the preference for and survivorship of D. citri adults on N. tabacum and their feeding behavior were investigated. The results showed that D. citri adults were attracted to N. tabacum and to the green leaf volatiles (GLVs) (Z)-3-hexenol and (E)-2-hexenol. The survival of D. citri adults on N. tabacum was less than 30 h, which was shorter than that for adults without food (35 h) and on a suitable host Murraya exotica L. (29 days). Electrical penetration graph (EPG) recordings revealed that the pathway phase of D. citri on N. tabacum leaves consisted of four waveforms—the non-probing phase (NP), the pathway phase (PP, including intercellular probing of activity in the phloem (C) and phloem penetration (D)), phloem salivation (E1), and phloem ingestion (E2). Diaphorina citri only secreted saliva and ingested sap from phloem on N. tabacum leaves and spent the longest duration in phloem sap ingestion (E2). Moreover, L-nicotine, an important defense compound against insects in N. tabacum plants, was highly toxic to D. citri. These results suggested that N. tabacum plants could help to sustainably control the spread of D. citri and HLB when growing in and around citrus orchards.